Assessment of Small Diameter Steel Pile as a Stabilizing Element for Transmission Tower Slope Stability - Katman H.Y.B.; Lee C.Y.; Zulnisyam D.U.; Baharuddin I.N.Z.; Pauzi N.I.M. (Bentham Science Publishers, 2024)
Background: Stabilization of unstable slopes with relatively large reinforced concrete piles has been widely adopted over the past several decades. Small diameter steel piles have several advantages as a slope reinforcement technique for an unstable transmission tower slope where space and access restrictions that typically occur render alternate approaches unfeasible. Methods: In this study, a numerical performance assessment of small diameter steel pile as a stabilizing element for transmission tower slope stability was carried out using an uncoupled analysis, in which the pile response and slope stability are considered separately. Numerical evaluations are presented and the influencing parameters that could affect the behavior of reinforcing piles to increase transmission tower slope stability are investigated. Results: The numerical analysis results indicate that the soil properties, slope geometry, pile location, pile diameter, pile length and number of pile rows have a combined effect on the performance of small diameter steel piles to stabilize transmission tower slopes. Conclusion: The numerical assessment can satisfactorily capture some fundamental response of transmission tower slope reinforced with multi-row small diameter steel piles. 2023 Katman et al.